Using fuzzy goal programming by considering personal preferences for job selection via the internet. Issue 6 (1st August 2016) - Chen, Chih-Yung; Su, Chia-Rong; Tu, Jih-Fu; Lin, Chang-Ching; Chang, Ching-Ter
Abstract : Purpose: – The purpose of this paper is to use a personal fuzzy demand and assists via the system computing to find a job for personal decisions, through job search system to achieve this methodology. Design/methodology/approach: – The search system uses the fuzzy goal programming (FGP) method by setting personal preferences property values and screening the data for comparison and calculation. Finally, through the presentation of information by sort and provide best suggestions. Findings: – Through FGP algorithms, it makes job search system to meet better for the needs of user, it can really react job seeker thinking to pursue job patterns. Research limitations/implications: – In this paper, considering the local cultural environment, so only limited to domestic of Taiwan as samples. Practical implications: – The experimental results of the proposed method compared with other website are presented to show the effectiveness. Originality/value: – This paper achieves personal decisions making via internet by FGP which is seldom studied.